Prefeeding of Clarias gariepinus with Spirulina platensis counteracts petroleum hydrocarbons-induced hepato- and nephrotoxicity - Alaa El-Din H. Sayed; Nasser S. Abou Khalil; Alshaimaa A. I. Alghriany; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Scientific Reports, 2024)
Abstract Petroleum aromatic hydrocarbons are considered one of the most dangerous aquatic pollutants due to their widespread across water bodies, persistence, and extension to the food chain. To our knowledge, there hasn’t been any research investigating the hepatorenoprotective effects of Spirulina platensis (SP) against toxicity induced by these environmental toxicants in fish. Thus, we decided to explore its potential safeguarding against benzene and toluene exposure in adult Clarias gariepinus. To achieve this objective, fish were divided into five groups (60 per group; 20 per replicate). The first group served as a control. The second and third groups were intoxicated with benzene and toluene at doses of 0.762 and 26.614 ng/L, respectively for 15 days. The fourth and fifth groups (SP + benzene and SP + toluene, respectively) were challenged with benzene and toluene as previously mentioned following dietary inclusion of SP at a dose of 5 g/kg diet for 30 days. The marked increase in liver metabolizing enzymes, glucose, total protein, albumin, globulin, albumin/globulin ratio, and creatinine confirmed the hepato- and nephrotoxic impacts of benzene and toluene. These outcomes were coupled with cytopathological affections and excessive collagen deposition. The incorporation of SP in ration formulation, on the contrary, restored the previously mentioned toxicological profile due to its antioxidant and cytoprotective attributes. Regardless of SP intervention, the renal tissues still displayed histo-architectural lesions, because of insufficient dose and timeframe. Additional research will be required to identify the ideal SP remediation regimen.